Factors leading to the adoption of blockchain technology in financial reporting - Saheb, Shaiku Shahida; Chinnapareddy, Venkata Krishna Reddy; Devalla, Divya; Charugulla, Sirisha; Chakka, Naga Bhavani; Raja Sekhar, Kunchakara (Frontiers in Blockchain, 2025)
IntroductionThe initiation of blockchain has brought about revolutionary changes across multiple industries, including finance. This study analyzes published research related to existing financial reporting and audit practices relevant to the implementation and efficacy of blockchain technology. The decentralized, immutable, and transparent blockchain ledger is set to change traditional practices by enhancing accuracy, reducing fraud, and ensuring real-time data accessibility.MethodsThis study identifies and measures the factors influencing blockchain implementation in specific auditing areas, particularly financial reporting. This research analyzed accounting professionals’ awareness of information and communication technologies (ICT), data security, data privacy, and training among accounting professionals. Hence, the study conducted a survey that targeted accounting practitioners, chartered accountants, financial analysts, and auditors with the aim of analyzing and testing hypothesized relationships using structural equation modeling in AMOS software.ResultsIt presents an empirical analysis that examines the extent to which these factors influence blockchain technology implementation in financial reporting and auditing. We found a significant influence of blockchain technology use on the practices of financial reporting and auditing, leading to enhanced accuracy and transparency, reduced audit time, and increased trust in financial reports. Key findings indicate that while blockchain technology offers significant advantages, widespread implementation faces hurdles such as regulatory compliance, technological integration, and stakeholder acceptance.DiscussionResearchers can use these findings to determine potential areas for further research. In addition, this research provides valuable information to practitioners in the field, academics, industry professionals, and policymakers considering the integration of blockchain technology with financial reporting and auditing.